2021
DOI: 10.31729/jnma.5413
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Medical Science Students' Positive Attitude towards Online Classes during COVID-19 Pandemic in a Medical College: A Descriptive Cross-sectional Study

Abstract: Introduction: The outbreak of COVID-19 led to lockdown, which in turn led to the closure of schools and colleges. This situation created an opportunity to transform the conventional learning methods into an online or virtual method using various digital platforms. Nepalese Army Institute of Health Sciences started online classes as an alternative way to resume education during this pandemic. Therefore, this study aims to identify the prevalence of medical science students with a positive attitude towards onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…11 Another study done in Nepal among 513 students during the COVID-19 pandemic showed 396(77%) students had a positive perception of online learning. 12 A study conducted in Egypt, among 350 students before the COVID-19 pandemic showed that 327(93.4%) students had satisfaction towards online learning 13 , Though, positive perception of nursing students in this study is not as high as other studies conducted in different countries, it might be alternative teaching-learning methods to continue online learning as a part of the nursing school teaching-learning curriculum beyond the COVID-19 pandemic situation.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…11 Another study done in Nepal among 513 students during the COVID-19 pandemic showed 396(77%) students had a positive perception of online learning. 12 A study conducted in Egypt, among 350 students before the COVID-19 pandemic showed that 327(93.4%) students had satisfaction towards online learning 13 , Though, positive perception of nursing students in this study is not as high as other studies conducted in different countries, it might be alternative teaching-learning methods to continue online learning as a part of the nursing school teaching-learning curriculum beyond the COVID-19 pandemic situation.…”
Section: Discussioncontrasting
confidence: 49%
“…Similarly, 252(72%) students from Egypt agreed that internet disrupted online classes. 12 Another study in Nepal showed that 640(63.2%) students experienced disturbance due to electricity problems. 20 effectiveness of online teaching is influenced by the quality of internet service and regular electricity supply.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to assess the usability of online learning methods, and to determine their feasibility and adequacy for medical students [9]. Many studies actually demonstrates the positive attitude of medical students of developed or under developed countries towards online learning [10][11][12]. Anatomists have therefore been challenged to unbolt technology in attempt to attain best deliverables for their discipline, without the use of traditional teaching aids such as the cadaver, osteological specimens, prosected specimens, models, and microscopic slides and shifted the methods to electronic based [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Other living areas could also limit internet access, considering participants in this study were spread all over the country. This could spend more mental effort with no significant information acquired on the related modules, thus affecting students’ self-efficacy [ 35 ]. It was also found that self-efficacy correlates to students’ knowledge [ 36 ].…”
Section: Discussionmentioning
confidence: 99%